The hydrodynamic of Dong River, Hutan Lipur Lata Jarum, Pahang, Malaysia - Muhammad Barzani, Gasim; Mohd Ekhwan, Toriman; Nor Azlina Binti, Abdul Aziz (2013)
The natural environment of Lata Jarum with its chilly cold water of waterfall is one of the local leisure spots in Raub, Pahang. The waterfall of Dong River is located within the virgin forest Benum Mountain (or in local name is Gunung Benum) - Hutan Lipur Lata Jarum. For the hydrology research, we have five sampling stations with four stations at the upstream and one at downstream. This research is carried out in order to study the hydrodynamic of Dong River. Observed data was carried on 16 to 17 November 2009. The results indicate that, the flow was ranged from 3.452 to 20.331m³/s while velocity of water was ranged from 0.128 up to 4.000m/s. The XP-SWMM modeling was used to study the hydrodynamic of the river. Simulation result showed that, the flow was ranged from 5.995 to 36.212 m³/s and the velocity was ranged from 3.46 to 9.32m/s. Through the study, we can predict; the high velocity of river water would lead to river flooding easily once rainfall has occurred due to several characteristics of the river such as fast river velocity, limited drainage capacity and hydraulic regime which found to be less tolerate with high volume of discharge